2014
DOI: 10.4103/2231-0762.149028
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologists′ knowledge and attitudes regarding oral health and periodontal disease leading to adverse pregnancy outcomes

Abstract: Objectives:A cross-sectional study was conducted to evaluate the knowledge and practiced behaviors of gynecologists regarding oral health care during pregnancy and the association of periodontal disease with adverse pregnancy outcomes.Materials and Methods:A questionnaire consisting of 16 questions was designed and pilot tested. One hundred and fifty gynecologists practicing in the private sector of United Arab Emirates (UAE) were approached to voluntarily participate and fill up the questionnaire during Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 13 publications
6
51
2
2
Order By: Relevance
“…Our findings also support earlier reports [3234, 40] about the misconceptions among ANC providers regarding oral health in pregnancy. Over half of ANC providers believed the myth that calcium will be drawn out of mothers’ teeth by the developing baby, and over a third falsely believed it is unsafe to obtain dental radiographs in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also support earlier reports [3234, 40] about the misconceptions among ANC providers regarding oral health in pregnancy. Over half of ANC providers believed the myth that calcium will be drawn out of mothers’ teeth by the developing baby, and over a third falsely believed it is unsafe to obtain dental radiographs in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…Over half of ANC providers believed the myth that calcium will be drawn out of mothers’ teeth by the developing baby, and over a third falsely believed it is unsafe to obtain dental radiographs in pregnant women. The respondents did however demonstrate sound knowledge about the safety of dental procedures during pregnancy, similar to previous studies [32, 40, 41]. Knowledge of safe medications during pregnancy was poor among ANC providers.…”
Section: Discussionsupporting
confidence: 78%
“…Many health professionals are aware of the importance of oral health, but often they do not address it as part of their provision of preconception, prenatal, or well woman care (Hashim & Akbar, 2014;Morgan et al, 2009). Hashim and Akbar found that 95.4% of gynecologists surveyed had knowledge about the association between oral health and pregnancy and that 85.2% recommended dental visits for their patients.…”
Section: Oral Health Practice Behavior Of Women's Health Care Providersmentioning
confidence: 99%
“…Surveys conducted in other regions of the world have shown that visits to the dentist during pregnancy are suggested by 44% to 93.9% of specialists [28][29][30][31][32]. A relation between the referral of pregnant women to the dentist and knowledge about the impact of oral health on pregnancy has been shown [31].…”
Section: Discussionmentioning
confidence: 99%
“…A number of physicians still consider it dangerous to perform certain diagnostic or therapeutic procedures during pregnancy, such as dental radiography and local anaesthesia [29]. In a study by Al-Habanesh et al, 81% of the doctors agreed that pregnancy caused gingival inflammation, but 88% advised patients to postpone treatment until after delivery.…”
Section: Discussionmentioning
confidence: 99%